Des spécialistes du (discours) direct ? - Jeanne VIGNERON-BOSBACH (E-REA)
In this article, we want to observe the English marker like and the French marker genre used within direct quotation contexts. We borrow descriptive tools from the « Approche pronominale » and the macrosyntax theories (Blanche-Benveniste, 1990, Deulofeu, 2003) in an attempt to analyse the syntactic relationship between on the one hand genre/like followed by a quote and on the other hand the quoting segment. Our goal is to determine whether these markers are syntactically micro-dependent from the quoting segment. Secondly, we examine the quotative complex verbs be like and faire genre in order to describe their syntactic features and to study the nature of the relationship between the quoting segment and the quote itself.